Proceso de atención de enfermería en recién nacido con disnea - Bajaña Cedeño, Rosa Ángela (2020)
The following document details information related to what has to do with respiratory distress in the newborn as concepts, causes of the problem, its clinical manifestations, how risk factors influence the diagnosis, its symptoms and above all, emphasizing in the nursing care that should be provided to patients with this pathology, since it is the reason why this work is carried out for the application of the nursing care process. This case is of vital importance and can serve as a guide for other health professionals since in the world of work we face a great challenge when caring for a newborn with respiratory distress and even more so when it comes to a newborn premature.